Associations of free sugars from solid and liquid sources with cardiovascular disease: a retrospective cohort analysis - Kaberi Dasgupta; Joseph Mussa; Anne-Sophie Brazeau; Mourad Dahhou; Claudia Sanmartin; Nancy A. Ross; Elham Rahme (BMC, 2023)
Abstract Background The World Health Organization recommends a 10% total energy (TE%) limit for free sugars (i.e., added sugars and naturally occurring sugars in fruit juice, honey, and syrups) based on evidence linking higher intakes with overweight and dental caries. Evidence for cardiovascular disease (CVD) is limited. Impacts may differ by sex, age group, and solid vs. liquid sources; liquids may stimulate more adverse CVD profiles (due to their rapid absorption in the body along along with triggering less satiety). We examined associations of consuming total free sugars ≥ 10 TE% with CVD within four sex and age-defined groups. Given roughly equal free sugar intakes from solid and liquid sources, we also evaluated source-specific associations of free sugars ≥ 5 TE% thresholds. Methods In this retrospective cohort study, we estimated free sugars from 24-h dietary recall (Canadian Community Health Survey, 2004-2005) in relationship to nonfatal and fatal CVD (Discharge Abstract and Canadian Mortality Databases, 2004-2017; International Disease Classification-10 codes for ischemic heart disease and stroke) through multivariable Cox proportional hazards models adjusted for overweight/obesity, health behaviours, dietary factors, and food insecurity. We conducted analyses in separate models for men 55 to 75 years, women 55 to 75 years, men 35 to 55 years, and women 35 to 55 years. We dichotomized total free sugars at 10 TE% and source-specific free sugars at 5 TE%. Results Men 55 to 75 years of age had 34% higher CVD hazards with intakes of free sugars from solid sources ≥ 5 TE% vs. below (adjusted HR 1.34, 95% CI 1.05- 1.70). The other three age and sex-specific groups did not demonstrate conclusive associations with CVD. Conclusions Our findings suggest that from a CVD prevention standpoint in men 55 to 75 years of age, there may be benefits from consuming less than 5 TE% as free sugars from solid sources.